PERUBAHAN KANDUNGAN KIMIA SARI ROSELA MERAH DAN UNGU (Hibiscus sabdariffa L.) HASIL PENGERINGAN MENGGUNAKANCABINET DRYER DAN FLUIDIZED BED DRYER - Mardiah, Fransiska Rungkat Zakaria, Endang Prangdimurti, Rizal Damanik TIP (Jurnal Teknologi Industri Pertanian, 2015)
Roselle leaves were dried to improve handling and increase its preservation. In this study, two methods of drying were used, i.e. cabinet dryer (60oC, 6 hours) and fluidized bed dryer (70oC, 1.5 hours) and two variety of roselles were used, i.e.red roselle and purple roselle. The result showed that drying process decreased the content of anthocyanin, vitamin C and antioxidant capacity compared withthose of fresh roselle. The cabinet dryer maintained more of anthocyanin than fluidized bed dryer. From both dryers, contents of anthocyanin and antioxidant capacity in purple roselle were higher than red roselle,but vitamin C content in red roselle was higher than that in purple roselle. The phytochemical analyses indicated that both of roselles contained flavonoid, steroid, triterpenoid, saponine, tannin and phenolhydroquinone.Keywords: cabinet dryer, fluidized bed dryer, anthocyanin, antioxidant capacity, roselle